Latent profile analysis of college students’ mental Huagong On the Horizon of Chinese Culture - Li, Li Bing-quan; Wu, Run-miao; Pang, Zi-shan (Technium Social Sciences Journal, 2024)
Objective: To explore the latent class characteristics of college students’ mental Huagong. Methods: A questionnaire survey was carried out on 510 college students by using Collage Mental Huagong Scale(CMHGS) and the Self-assessment Scale of College Students’ Innovation and Entrepreneurship Ability(CSIEASAS). Results: The college students’ mental Huagong can be divided into high Huagong group (40%), high-level low will group (6%), medium-level low emotion group (48%) and low Huagong group (5%). There were significant differences in the scores of entrepreneurial personality, basic entrepreneurial ability, core entrepreneurial ability and social adaptability among the four Latent class model of collage students’ mental Huagong. Conclusion: There are four Latent class model of college students’ mental Huagong , and there are significant differences in each dimensions of college students’ abilities of innovation and entrepreneurship among each latent class models of college students’ mental Huagong.